Analisis Kualitas Fisik dan Bakteriologi (E-Coli) Air Sumur Gali Di Jorong Koto Kaciak Kanagrian Magek Kecamatan Magek - Syukra Alhamda; Mila Sari; Nova Herawati (Jurnal Sehat Mandiri, 2021)
Jorong Koto Kaciak is a fairly high incidence of diarrhea contributed 36% of the incidence of diarrhea in Magek District. This study aims to analyze the Physical Quality and Bacteriology (E-Coli) of Dug Well Water in Jorong Koto Kaciak. This is a descriptive describing the physical quality and bacteriology of community dug well water. The populations were all community dug wells amount 153 units. By using cluster sampling, the sample was determined as much as 5 dug wells. Data collection used observation sheets and data analysis included univariate analysis which was carried out computerized. The results showed that 80% dug well water samples met the physical parameter requirements based on temperature, overall 100% community dug well water met the turbidity requirements <25 NTU / 100 ml, 60% dug well water samples met the physical requirements. odorless and tasteless and overall 100% dug well water samples do not meet the quality requirements of microbiology (e-coli)> 50 MPN / 100 ml It can be concluded that the community dug well water physically meets the quality standard requirements drinking water, but microbiologically it does not meet the health standard requirements, especially the quality of bacteriology, which can increase the risk of gastrointestinal infections for the community (diarrhea). For this reason, it is recommended that the community and health workers in Jorong Koto Kaciak pay more attention to the quality of dug well water.